Estratégias para melhorar o nível de maturidade da Governança de Tecnologia da Informação - Rodello, Ildeberto Aparecido; Bonardo, Flávio Sergio (Journal on Advances in Theoretical and Applied Informatics; Vol 3 No 2 (2017): Journal on Advances in Theoretical and Applied InformaticsDO - 10.26729/jadi.v3i2.2211, 2017)
Companies are stranding resources and losing competitiveness in due to do not implementing the processes of effective Information Technology Governance. Assess the current level of maturity and define strategies to achieve the desired level are important steps for managers and executives in order to promote the alignment between business and IT. This paper presents the results of a research to identify the level of maturity in Telecom department in a large Brazilian bank, setting a desired level of maturity and indicate strategic actions to reach it. Guided by COBIT®, was identified the current maturity level and actions was proposed to achieve the desired one. In robust organizational structures, it is possible to verify that the local analysis of governance maturity can aid managers for planning aligned departmental efforts to executive strategy for IT and business, bringing major effectiveness